2021
DOI: 10.1155/2021/8987232
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Effects of the Aqueous Extract from Taraxacum officinale in Rats Using Ultrasound, Histology, and Biochemical Analysis

Abstract: Taraxacum officinale F.H. Wigg. belonging to the family Asteraceae is an edible medicinal plant distributed worldwide. This study aimed to determine the gastroprotective effects of aqueous extract of T. officinale (AETo) in rats using ultrasound, histological, and biochemical analyses. In this study, gastric ulceration was induced by ethanol or piroxicam. Rats were then treated with AETo (3, 30, or 300 mg/kg). The area and histological appearance of gastric ulcers were quantified, and histochemical analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…(2021) reported that the aqueous extract of Taraxacum officinale increased the levels of SOD, CAT, GSH and GST in rats and decreased the levels of myeloperoxidase. The same researchers stated that Taraxacum officinale extract can also prevent the thinning of the gastric wall by decreasing the ulcerative areas and increasing the mucin level [20]. In this study, it was determined that indomethacin caused significant damage to the stomach tissue, whereas Taraxacum officinale leaf ethanol extract, given orally to rats for 10 days before indomethacin administration, reduced the formation of ulcerative areas just like a standard drug, omeprazole.…”
Section: Discussionmentioning
confidence: 85%
“…(2021) reported that the aqueous extract of Taraxacum officinale increased the levels of SOD, CAT, GSH and GST in rats and decreased the levels of myeloperoxidase. The same researchers stated that Taraxacum officinale extract can also prevent the thinning of the gastric wall by decreasing the ulcerative areas and increasing the mucin level [20]. In this study, it was determined that indomethacin caused significant damage to the stomach tissue, whereas Taraxacum officinale leaf ethanol extract, given orally to rats for 10 days before indomethacin administration, reduced the formation of ulcerative areas just like a standard drug, omeprazole.…”
Section: Discussionmentioning
confidence: 85%
“…The slices were analyzed by an independent pathologist in a blind manner. Further, the remaining histological slides were used for histochemical analysis of mucins using the periodic acid Schiff (PAS) method, which stains glycoproteins like mucins in pink, as earlier performed [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Food was withdrawn 12 h before the experiments and water was provided ad libitum. Several studies performed in female rodents at different stages of the estrous cycle have shown no interference in the results [ 40 , 41 ]. The experiments were conducted following ARRIVE guidelines and the National Council for Animal Experimentation (CONCEA) after approval by the Institutional Animal Ethics Committee of Unochapecó (protocol number 014/18).…”
Section: Methodsmentioning
confidence: 99%